ANALISIS FAKTOR-FAKTOR PEMILIHAN KONTRASEPSI TERHADAP PENCAPAIAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI KECAMATAN MEDAN SUNGGAL - Dimas Hernowo (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2025)
The achievement of Long-Acting Contraceptive Methods (LACM) in the District of Medan Sunggal is still relatively low. This low achievement can be attributed to several factors influencing contraceptive selection. Factors determining contraceptive choice among Fertile Age Couples (FAC) include age, employment status, number of children, mother's education, family income, knowledge, quality of family planning services, and husband's support. This research aims to determine: (1) variations in contraceptive method selection in the District of Medan Sunggal; and (2) the relationship between factors influencing contraceptive selection and the achievement of LACM; (3). This study employs a quantitative method with univariate and bivariate analyses. Data analysis from 97 respondents shows: (1) 80 respondents use Non-LACM and 17 respondents use LACM; (2) variables significantly related are age (0.006), number of children (0.001), family income (0.015), knowledge (0.007), and husband's support (0.000) (p-value < 0.05).